2018
DOI: 10.1002/mgg3.390
|View full text |Cite
|
Sign up to set email alerts
|

Structural variations causing inherited peripheral neuropathies: A paradigm for understanding genomic organization, chromatin interactions, and gene dysregulation

Abstract: Inherited peripheral neuropathies (IPNs) are a clinically and genetically heterogeneous group of diseases affecting the motor and sensory peripheral nerves. IPNs have benefited from gene discovery and genetic diagnosis using next‐generation sequencing with over 80 causative genes available for testing. Despite this success, up to 50% of cases remain genetically unsolved. In the absence of protein coding mutations, noncoding DNA or structural variation (SV) mutations are a possible explanation. The most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 100 publications
(127 reference statements)
0
22
0
1
Order By: Relevance
“…14,17 Besides the common PMP22 rearrangements, pathogenic copy number variants are known in MPZ, GJB1, MFN2 (in compound heterozygous state with a second pathogenic mutation), NDRG1, GAN, and SEPT9. 32,33 More recently, a 78-kb duplication of chromosome 8q24.3 locus at chromosome Xq27.1 and a 1.35-Mb duplication of chromosome 7q36.3 were identified as the cause of CMTX3 and dHMN1, respectively. 32 Our study identified novel pathogenic copy number variants in FDG4 and SH3TC2 and suggest that implementation of NGS panels in a diagnostic setting will lead to an increased identification of structural variants in known CMT genes.…”
Section: Discussionmentioning
confidence: 99%
“…14,17 Besides the common PMP22 rearrangements, pathogenic copy number variants are known in MPZ, GJB1, MFN2 (in compound heterozygous state with a second pathogenic mutation), NDRG1, GAN, and SEPT9. 32,33 More recently, a 78-kb duplication of chromosome 8q24.3 locus at chromosome Xq27.1 and a 1.35-Mb duplication of chromosome 7q36.3 were identified as the cause of CMTX3 and dHMN1, respectively. 32 Our study identified novel pathogenic copy number variants in FDG4 and SH3TC2 and suggest that implementation of NGS panels in a diagnostic setting will lead to an increased identification of structural variants in known CMT genes.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low ratio of positively verified CMT cases may be associated with structural variations that are not detectable in routine molecular analysis, expanding the mutation spectrum of existing CMT variants. These structural variations encompass both large translocations (e.g., a 1.35 Mb inversion on chromosome 7q36.3) and relatively small duplications (e.g., 118 kb, 6.25 kb) [9]. However, the list of genes responsible for CMT disease seems to be far from complete.…”
Section: Genetic Background Of Charcot-marie-tooth Diseasementioning
confidence: 99%
“…Charcot-Marie-Tooth (CMT) diseases are the group of inherited neuropathies caused by chromosomal rearrangements and mutations 1 , 2 . Demyelinating CMT1A occurs in the first and second decade of life and represents around 40–60% of all CMT cases 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%